Public Enemies - The Golden Age of the Gangster Film - Nasr, Constantine; Baldwin, Alec (Warner, 2008)
As popular as the classic gangster movies were in their heyday, originals like "Little Caesar" and "The Public Enemy" as well as postwar gems like "Key Largo" and "White Heat" still hold power over their audiences today. Explore the invention and development of the crime genre from the turn of the century to the silent era; the rise of Warner Bros. Stars like James Cagney, Humphrey Bogart and Edward G. Robinson; directors like Michael Curtiz, Raoul Walsh and William Wellman; the films themselves and the influence they had on filmmakers all over the world; and the artistic merit these defining classic films still warrant. Learn about the effect of Prohibition, Censorship, the Depression and World War II on the rise of criminality in society - and its subsequent reflection on-screen. [Cover]